Impact of natural killer cells on chronic hepatitis C and hepatocellular carcinoma. Issue 5 (30th January 2016) - Tatsumi, Tomohide; Takehara, Tetsuo
Abstract : Natural killer (NK) cells are involved in the pathogenesis of hepatitis C viral (HCV) infection and hepatocellular carcinoma (HCC). Recent immunological progresses have revealed the molecular mechanisms of activation or inhibition of NK cells. In patients infected with HCV, the percentages of NK cells are decreased and the NK receptor expression and function of NK cells including cytotoxicity and cytokine production are altered. These alterations in NK cells are associated with persistent infection with HCV, liver injury, liver fibrosis and liver carcinogenesis. In HCV treatment, NK cells play a role in the eradication of HCV in both interferon (IFN)‐based therapy and IFN‐free therapy using direct‐acting antivirals (DAA). In HCC patients, the exhaustion of NK cells that represents lower cytotoxicity and impaired cytokine production may contribute to the progression of HCC. Several immunotherapies targeting NK cells have been reported. NK cell transfer and NK‐activating gene therapy have been demonstrated to be effective in mouse liver cancer models and several clinical trials are ongoing. Recently, the role of major histocompatibility complex class I‐related chain A (MICA), a human ligand of NKG2D, has attracted attention in the development of HCC. The expression of MICA could be controlled by anti‐HCC drugs including sorafenib. A new chemo‐immunotherapy may be expected in the treatment of HCC. In this review, we summarize the impact of NK cells on chronic hepatitis C and HCC.